2001
DOI: 10.1159/000055694
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of Human Lens Epithelial Cells in vivo

Abstract: We examined the density and morphology of lens epithelial cells (LECs) in vivo in a group of normal volunteers and cataract patients by using a newly developed noncontact specular microscope. There was a statistically significant decrease in the cell density of LECs in a group of cataract patients over the age of 80 years. The coefficient of variation of the cell area and the number of large black spots that were observed in the enhanced specular images were not related to aging or cataract formation. Our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
1
0
2
Order By: Relevance
“…Similar to previous studies in mouse and human lenses[54,[100][101][102], we observe increased epithelial cell area with age. We have recently shown that lens shape change requires epithelial cell expansion[53].…”
supporting
confidence: 91%
“…Similar to previous studies in mouse and human lenses[54,[100][101][102], we observe increased epithelial cell area with age. We have recently shown that lens shape change requires epithelial cell expansion[53].…”
supporting
confidence: 91%
“…There are many ways wound healing and unjamming may take place at different densities in vivo. For example, cell density of lens epithelium [40] and corneal endothelium [41] decreases significantly with age. Also, epithelium persistently exposed to drugs and infection shows a lower cell density than healthy epithelium [42].…”
Section: Discussionmentioning
confidence: 99%
“…Γενικά, στον γεροντικό καταρράκτη, έχει αναφερθεί ένας πολύ χαμηλός δείκτης μίτωσης της τάξης του 0,0004% 60 , αν και υψηλότεροι δείκτες μίτωσης της τάξης μέχρι και του 0,008% έχουν αναφερθεί τόσο σε φυσιολογικούς όσο και καταρρακτικούς φακούς 51 . Εντούτοις, πειραματικές μελέτες σε ζώα, έχουν καταδείξει ότι τα επιθηλιακά κύτταρα στην κεντρική ζώνη ανταποκρίνονται σε ποικίλα μιτωτικά ερεθίσματα, όπως το τραύμα 54,55,[61][62][63][64][65][66][67][68][69][70][71][72] , οι ορμόνες 69,70,71 , και η πειραματική ραγοειδίτιδα 72,73,74,75 Στον ανθρώπινο κρυσταλλοειδή φακό, το ασκορβικό οξύ ανιχνεύεται σε υψηλή συγκέντρωση, που μερικές φορές ξεπερνά τη αντίστοιχη συγκέντρωση στο υδατοειδές υγρό 188 . Τα ασκορβικό οξύ δεν συντίθεται στον φακό, αλλά υπάρχουν αποδείξεις ότι υπάρχει εξειδικευμένο σύστημα μεταφοράς του ασκορβικού οξέος, από τα περιβάλλοντα υγρά προς το εσωτερικό του φακού 189,190 .…”
Section: εμβρυολογικά στοιχεία του φακούunclassified
“…Η κύτταρο-κερατίνη είναι Τέλος, αναφέρουμε ότι πρόσφατες μελέτες που έγιναν με την χρησιμοποίηση του φασματοσκοπικού μικροσκοπίου, επέτρεψαν την, in vivo, δίκην "μωσαϊκού", παρατήρηση του πρόσθιου επιθηλίου του φακού, σε ασθενείς με καταρράκτη29 . Το φακικό επιθήλιο θεωρείται ότι είναι το πιο ενεργά, μεταβολικό συστατικό του κρυσταλλοειδούς φακού70,71,72 . Έχει αποδειχτεί, ότι αποτελεί τον πρωτεύοντα ιστό που προσβάλλεται σε μερικούς τύπους καταρράκτη, όπως είναι στον από ακτινοβολίας και από ηλεκτροπληξίας καταρράκτη.…”
unclassified